Renaissance values - Yakimenko, Ylyana Igorivna; Povolotska, G. G. (Видавництво НТУ "ДП", 2023)
The Renaissance was possibly the most important period of development that has ever occurred in European history. Known primarily for its impact on the art world, the Renaissance emerged as a movement that influenced literature, philosophy, music, science, and even technology. With the impacts of the Renaissance still felt in society today, it unquestionably remains one of the most spoken-about and celebrated movements in both the artistic and general community.
Keywords: Ренесанс; епоха Відродження; література та культура епохи Відродження